Formation of tissue factor-factor VIIa-factor Xa complex induces activation of the mTOR pathway which regulates migration of human breast cancer cells - Jiang, Xiaofeng; Zhu, Shimei; Panetti, Tracee S.; Bromberg, Michael E. (Thrombosis and Haemostasis, 2008)
Tissue factor (TF) is a transmembrane glycoprotein that initiates blood coagulation when complexed with activated factor VII (FVIIa).TF is constitutively expressed in a variety of tumor cells and has been implicated in cellular signaling, angiogenesis, and tumor progression. Formation of TF-FVIIa complex and generation of downstream coagulation proteases, including activated factor X (FXa) and thrombin, initiate signaling by activation of protease-activated receptors (PARs).We have previously shown thatTFFVIIa-Xa complex formation promotes phosphorylation of p44/42 mitogen-activated protein kinase and Akt/protein kinase B in human breast cancer cells. In the present study, we show that formation of TF-FVIIa-FXa complex induces phosphorylation of mammalian target of rapamycin (mTOR) and p70 S6 kinase in a human breast cancer cell line, Adr-MCF-7. Activation of the mTOR pathway, which is probably mediated by PAR1 and/or PAR2, was associated with enhanced cell migration, a key step in the metastatic cascade. Inhibition of this pathway with the specific mTOR inhibitor, rapamycin, markedly decreased cell migration induced by formation of TFFVIIa-FXa complex. These studies suggest thatTFFVIIa-mediated signaling modulates mTOR pathway activation, which regulates in part breast cancer cell migration. Targeting the TF-mediated cell signaling pathway might represent a novel strategy for the treatment of breast cancer.
Keywords: Tissue factor; factor VIIa; factor Xa; mammalian target of rapamycin; breast cancer